2012
DOI: 10.1007/s00381-012-1748-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the implantation of Ommaya reservoir in children with tuberculous meningitis hydrocephalus: a preliminary study

Abstract: Ommaya reservoir implantation has been shown to be effective in treating children with TBMH. This method may be largely suitable for children with early grade II TBM or partly in children with grade III TBM who have mild or moderate hydrocephalus that can alleviate after short-term treatment. Thus, a good proportion of children who undergo Ommaya reservoir implantation can avoid ventriculoperitoneal shunt surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The most direct route to the CNS is to inject the drug into the intraventricular, intracavitary, or interstitial system. For example, intracerebroventricular (ICV) administration is considered as an intrathecal delivery via an ICV port implanted under the scalp of the patient and is used for treating various types of CNS diseases, such as infections [231,232], chronic pain [233,234], and types of brain cancer [235]. This local delivery ensures high drug concentrations in the CNS while the peripheral exposure is minimal.…”
Section: Direct Central Deliverymentioning
confidence: 99%
“…The most direct route to the CNS is to inject the drug into the intraventricular, intracavitary, or interstitial system. For example, intracerebroventricular (ICV) administration is considered as an intrathecal delivery via an ICV port implanted under the scalp of the patient and is used for treating various types of CNS diseases, such as infections [231,232], chronic pain [233,234], and types of brain cancer [235]. This local delivery ensures high drug concentrations in the CNS while the peripheral exposure is minimal.…”
Section: Direct Central Deliverymentioning
confidence: 99%
“…This route of administration, also referred to as intraventricular administration, has been used for several decades to provide treatments for pediatric and adult patients who suffer from a broad range of diseases, including infectious meningitis, intractable pain, and various types of cancer. [1][2][3][4][5] In addition to the ICV route, intrathecal delivery methods include single or repeated intrathecal lumbar (IT-L) injections, in which agents are directly administered into the cerebrospinal fluid (CSF) by puncturing the membranes surrounding the spinal cord (Fig 1). Intrathecal routes of administration allow therapies to bypass the bloodebrain barrier (BBB) and are commonly used to treat a variety of diseases in pediatric and adult patients.…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported 12 serious TBM cases, in pediatric age group, presenting with hydrocephalus and disturbed consciousness. All of them received IT injection of INH and dexamethasone, and a successful recovery was observed in 9 out of 12 patients [25]. In another study, Swift et al treated 18 TBM patients with IT isoniazid.…”
Section: Discussionmentioning
confidence: 99%